(untitled) (Journal of Pharma Insights and Research, 2025)
Religious fasting practiced within major world religions have garnered significant scientific interest due to their potential role in cancer prevention and treatment. These traditional practices induce metabolic alterations similar to those observed in therapeutic fasting protocols, including enhanced autophagy, reduced inflammation, and hormonal modulation. Cellular mechanisms activated during religious fasting periods demonstrate promising anti-cancer effects through multiple pathways. The practice triggers significant reductions in insulin and insulin-like growth factor 1 (IGF-1) levels, enhances cellular repair mechanisms, and modulates immune system function. Studies reveal that fasting-induced metabolic reprogramming creates an environment that may inhibit cancer cell proliferation while protecting healthy cells. Clinical investigations suggest that religious fasting can complement conventional cancer therapies by potentially enhancing treatment efficacy and reducing adverse effects. The widespread acceptance and cultural integration of religious fasting offer unique advantages for implementing health interventions, particularly in communities where traditional medical approaches face cultural barriers. However, the diversity in fasting protocols across different faiths necessitates careful consideration of individual practices and their specific physiological impacts. Emerging evidence from both preclinical and clinical studies supports the potential of religious fasting as a cost-effective, culturally acceptable approach to cancer prevention and treatment. Using these traditional practices with modern oncology presents opportunities for developing novel therapeutic strategies. Current research is aimed at standardizing fasting protocols, establishing safety guidelines for cancer patients, and investigating long-term effects on cancer prevention, marking an important convergence of traditional wisdom and modern medicine in oncology